(untitled) (Global Journal of Computer Science and Technology, 2021)
In a country where leaders are elected by the people, election, and the process of electing play a crucial role. Every citizen of a country has the right to vote. There are different ways of casting a vote and electing an individual. With such a large population, the country needs its own effective and secure voting system. The voting system has made drastic changes from traditional paper ballot voting to current electronic voting and now the online voting system. Advancements in the new system eliminate the drawbacks of the previous system. This paper proposes a new online voting system that provides every individual to cast a vote securely and effectively irrespective of the location.